Application of AIR Learning Model to Understanding the History of the Establishment of the Abbasiyah Dynasty - Wahyu Hidayat (UMSU, 2022)
This study purpose to determine the effect of the Auditory, Intellectually, Repitition (AIR) learning model on the historical understanding of the students' abbasid dynasty. This study uses a quantitative approach, in which data collection uses a test description instrument. The analysis technique in this research is descriptive analysis (mean and standard deviation) and t-test analysis to test differences in understanding of the material. The results of this study indicate that in the implementation of the AIR and students 'understanding is categorized as high 0.97 or 97%, it is said to be high because the implementation of the Auditory, Intellectually, Repitition (AIR) learning model can improve students' understanding. on learning Islamic Cultural History. There is an effect of the Auditory, Intellectually, Repitition (AIR) learning model on students' understanding of the learning of the history of the establishment of the Abbasid Dynasty class XI MIA.3 MAN 2 Barru.